Foliar Application of Di-Ammonium Phosphate and Triple Super Phosphate on Lentil at Drought Prone Area of Bangladesh (Journal of Bangladesh Academy of Sciences, 2018)
A field experiment was conducted to investigate the effect of foliar application of DAP and TSP on yield and yield attributing characters of lentil. Foliar application of DAP and TSP was performed at flowering and pod formation stages of lentil. Results revealed that maximum fresh weight of plant, nodule number and dry weight of nodule were recorded in F2 treatment at 50% flowering stage of lentil. F1 treatment produced higher branch plant-1 (2.66), pod plant-1(106.47) and seed yield (0.72 t ha-1) of lentil. DAP increased 6% higher grain yield than no foliar application of fertilizer. It may be suggested that foliar application of DAP is a better technology for increasing lentil production in drought prone area of Bangladesh.Journal of Bangladesh Academy of Sciences, Vol. 42, No. 2, 211-214, 2018